The role of digital leaders’ emotional intelligence in mitigating employee technostress - Ertiö, Titiana; Eriksson, Taina; Rowan, Wendy; McCarthy, Stephen (Elsevier, 2025)
Digital leadership involves dealing with complex challenges and anticipating trends that arise from emerging technologies. Amid the accelerated pace of digital transformation, consequences such as technostress have become apparent to organizations and their leaders. Emotional intelligence (EI) is an essential characteristic for enabling digital leaders to hone the necessary skills to lessen employees’ technostress by developing higher levels of consciousness of emotions—both one's own and those of others. By synthesizing research-based knowledge of EI and leadership, we contribute to a broader understanding of competency requirements for digital transformation by bringing employees and the role of digital leadership through EI into the picture. This article also presents new EI strategies for digital leaders to mitigate employee technostress in digital transformation via communication, transparency, and trust.